rabies virus monitoring in bats from the direct area of influence of hydroelectric power plant in Jirau, Rondônia, Brazil (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
In Rondônia State, North region of Brazil is being built at Madeira River, the hydroelectric power plant of Jirau. The implementation of huge enterprises such as the hydroeletric demands a series of alterations in the environment, such as vegetation suppression and movement of land in large extension along with other antropic activities of high environmental impact. These activities can destroy the artificial and natural shelters for bats. Several studies have pointed an association between these environmental changes and outbreaks of rabies. Monitoring Jirau´s bat population began in 2010 and it was made over a period of three years, with regular visits lasting 10 to 12 days, twice a year, totalizing six campaigns. First, the local population was interviewed aiming at eliciting what they knew about rabies and bats and to locate the shelters of these animals. In the period of three years, 158 people were interviewed, 4.387 bats were captured by mist net or active search and 3.852 of them were loose after this proceeding. Regarding to rabies, 535 bats and 486 sera were sent for diagnosis and antibodies dosage respectively at CCZ-SP by Direct Fluorescence and Simplified Fluorescence Inhibition Microtest. All bats were negative to rabies. The global prevalence of antibodies was 15.4% using 0.5IU/ ml as a cut-off (0% in the first campaign, 2.8%, 6.4%, 19.2%, 14.8% and 36.3% in the subsequent campaigns). In the interview 93.5% declared to know the disease, however rabies was associate to dogs and just 52.5% knew that bats could transmit rabies. Regarding the type of houses, 93.5% were vulnerable to bats presence and bats were roosting in 70% of these houses. The results for rabies antibodies dosage showed a progressive increase for every subsequent campaign. As the first campaign was performed before the demolition of the houses and vegetation suppression in the direct area of influence of the hydroelectric, these results could be reflecting the perturbation inflected to the population of bats such as the stress of the forced migration to search for new shelters and foraging areas as well as the disputes for space and food with the bats populations already established in the new shelters up to the moment when there is the reestablishing of the colonies. Considering just the presence of antibodies as indicative of the contact with the virus, the average of titers in the first and second campaigns was 0,03UI/ml and 0,04UI/ml while in subsequent campaigns this average was 0,21UI/ml, 0,49UI/ml, 0,24UI/ml and 0,38UI/ml, respectively. When statistically analyzed by Kruskal-Wallis (H=1.611,942; p